Cognitive and pragmatic approach to using stylistic devices in English literary discourse - Elena Monakhova (Peoples' Friendship University of Russia (RUDN University), 2019)
Modern linguistics does not treat language as an autonomous object of study, but takes an integrated approach to considering the way various factors affect the functioning of different linguistic phenomena within a discourse. Discourse analysis addresses spoken and written texts with regard to a situational context, cultural and historical background, ideological, social and psychological factors, as well as communicative, pragmatic and cognitive aims of the author, which in its turn determines the choice of language units. Literary discourse is an interaction between the author and the reader designed to generate emotional response. It relies on cultural, aesthetic and social values, background knowledge and worldview, beliefs, assumptions and feelings, and uses stylistic devices to produce the desired effect. This study gives evidence of the complex use of cognitive and pragmatic aspects in the analysis of stylistic devices in literary discourse. This approach makes it possible to analyse linguistic factors traditionally represented in linguo-stylistics, and consider extralinguistic parameters in order to better understand the way stylistic devices operate in the given type of discourse.